2019
DOI: 10.1002/lt.25666
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and Liver Disease in Children: Implications for Management Before and After Liver Transplantation

Abstract: There is close interaction between the functions of the liver and heart affecting the presentation, diagnosis, and outcome of acute and chronic cardiac and liver disease. Conditions affecting both organ systems should be considered when proposing transplantation because the interaction between cardiac disease and liver disease has implications for diagnosis, management, selection for transplantation, and, ultimately, for longterm outcomes after liver transplantation (LT). The combination of cardiac and liver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…3,4 Not only the risk of NAFLD and related complications need to be considered in children, but also genetic and metabolic conditions, as well as preparation and follow-up of liver transplantation, especially in the presence of multiorgan involvement. 5 In this complex landscape of pediatric liver disease and related metabolic disorders, it is crucial to develop noninvasive methods as alternatives to liver biopsy for the diagnosis, and perhaps more important, the monitoring of disease progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Not only the risk of NAFLD and related complications need to be considered in children, but also genetic and metabolic conditions, as well as preparation and follow-up of liver transplantation, especially in the presence of multiorgan involvement. 5 In this complex landscape of pediatric liver disease and related metabolic disorders, it is crucial to develop noninvasive methods as alternatives to liver biopsy for the diagnosis, and perhaps more important, the monitoring of disease progression.…”
mentioning
confidence: 99%
“…Additionally, multiple studies have shown the long‐term predictive role of increased childhood body mass index for adult‐age cirrhosis and hepatocellular carcinoma 3,4 . Not only the risk of NAFLD and related complications need to be considered in children, but also genetic and metabolic conditions, as well as preparation and follow‐up of liver transplantation, especially in the presence of multiorgan involvement 5 …”
mentioning
confidence: 99%